2005
DOI: 10.1074/jbc.m500775200
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Stimulatory Factors (USF-1/USF-2) Regulate Human cGMP-dependent Protein Kinase I Gene Expression in Vascular Smooth Muscle Cells

Abstract: Cyclic GMP-dependent protein kinase I plays a pivotal role in regulating smooth muscle cell relaxation, growth, and differentiation. Expression of the enzyme varies greatly in smooth muscle and in other tissues and cell types, yet little is known regarding the mechanisms regulating cGMP-dependent protein kinase gene expression. The present work was undertaken to characterize the mechanisms controlling kinase gene expression in vascular smooth muscle cells. A 2-kb human cGMP-dependent protein kinase I 5-noncodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…USF1 was reported to be able to combine with E-box sequence in the promoter of cathepsin B and increase its promoter activity as well as expression, and accordingly regulate the invasion and development of tumor (Yan et al, 2003). In human vascular smooth muscle cells, USF1 not only bound to E-box sequence in the promoter of cGMP dependent protein kinase 1 but also increased its promoter activity and expression, and thus regulated the growth and differentiation of vascular smooth cell (Sellak et al, 2005). Besides, USF1 participated in the transcription of ~40 kinds of cardiovascular related genes (Kristiansson et al, 2008), whereas the regulatory effect of USF1 on vascular endothelial cells still needs more research.…”
Section: Discussionmentioning
confidence: 99%
“…USF1 was reported to be able to combine with E-box sequence in the promoter of cathepsin B and increase its promoter activity as well as expression, and accordingly regulate the invasion and development of tumor (Yan et al, 2003). In human vascular smooth muscle cells, USF1 not only bound to E-box sequence in the promoter of cGMP dependent protein kinase 1 but also increased its promoter activity and expression, and thus regulated the growth and differentiation of vascular smooth cell (Sellak et al, 2005). Besides, USF1 participated in the transcription of ~40 kinds of cardiovascular related genes (Kristiansson et al, 2008), whereas the regulatory effect of USF1 on vascular endothelial cells still needs more research.…”
Section: Discussionmentioning
confidence: 99%
“…MEFs were incubated 4 hours at 37°C with 2 mL Opti-MEM medium containing complexes of 2 L of Lipofectamine, 0.1 g of human PKG-I reporter, 28 and 0.01 g of Renilla luciferase reporter as an internal control. The transfected cells were then incubated with complete growth medium for 24 hours, washed with PBS, and lysed.…”
Section: Transient Transfection and Luciferase Assaysmentioning
confidence: 99%
“…And Oct-1 represses p15 INK4b which functions as a tumor suppressor and implicated in cellular senescence and gadd45 (growth arrest and DNA damage-indueible genes) expression in an HDAC-dependent manner (Hirose et al 2003;Hitomi et al 2007). The overexpression of USF-1 and USF-2 has been reported to increase cGMP-dependent protein kinase I promoter activity in smooth muscle cell (Sellak et al 2005). However, it has also been reported that Nkx-2 plays an important role in myocardial cells (Thomas et al 2001;McKinsey 2007).…”
Section: Discussionmentioning
confidence: 95%